2017
DOI: 10.1002/2017gl074959
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cenozoic Subsidence in the Gulf of Mexico Resulting From Hess Rise Conjugate Subduction

Abstract: Enigmatic surface deflections occurred in North America starting from the Cretaceous, including the continental-scale drainage reorganization and the long-wavelength subsidence in the Western Interior Seaway. These surface undulations cannot be simply explained by sea level change or flexure loading. Coinciding with the large-scale surface deflection, the Gulf of Mexico (GOM) has an immense Paleocene sediment deposition probably caused by tectonic subsidence. Increasing evidence indicates a distinct seismic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Earlier studies of North American drainage evolution and sediment records in the Gulf of Mexico (GOM; Blum & Pecha, ; Galloway et al, ) suggested that the flow direction of the ancestral Mississippi switched from west‐northwest to east‐southeast since the Cretaceous and that the Cenozoic depocenter in the GOM migrated eastward through time. These observations, combined with this study, support the existence of a continental‐scale, temporally evolving subsidence signal, which is consistent with an eastward migratory wave of dynamic subsidence caused by the sinking Farallon slab (Liu, ; Wang et al, ). A detailed study of this is the subject of future research.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Earlier studies of North American drainage evolution and sediment records in the Gulf of Mexico (GOM; Blum & Pecha, ; Galloway et al, ) suggested that the flow direction of the ancestral Mississippi switched from west‐northwest to east‐southeast since the Cretaceous and that the Cenozoic depocenter in the GOM migrated eastward through time. These observations, combined with this study, support the existence of a continental‐scale, temporally evolving subsidence signal, which is consistent with an eastward migratory wave of dynamic subsidence caused by the sinking Farallon slab (Liu, ; Wang et al, ). A detailed study of this is the subject of future research.…”
Section: Discussionsupporting
confidence: 89%
“…For large T e values (>50 km), we do observe a limited amount (<100 km) of oceanward shift of the depocenter (Figures C and D), implying the occurrence of progradation, but this also results in significantly reduced sediment thickness, potentially inconsistent with the thick western GOM strata. Therefore, our results disfavor the hypothesis of oceanward sediment progradation within the GOM and support dynamic subsidence due to the sinking Farallon slab (Liu, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Deep into the mantle, the subducted Farallon slab has contributed to the Cenozoic tectonism in the CEUS (Liu, ; H. Wang et al, ; X. Wang et al, ). Some large‐scale geological features have been attributed to the eastward migration of the Farallon slab, such as the Cenozoic topography of the CEUS, the Miocene rejuvenation of the Appalachian Mountains, and the continental‐scale drainage reorganization (Blum & Pecha, ; Liu, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Deep into the mantle, the subducted Farallon slab has contributed to the Cenozoic tectonism in the CEUS (Liu, ; H. Wang et al, ; X. Wang et al, ). Some large‐scale geological features have been attributed to the eastward migration of the Farallon slab, such as the Cenozoic topography of the CEUS, the Miocene rejuvenation of the Appalachian Mountains, and the continental‐scale drainage reorganization (Blum & Pecha, ; Liu, ; Wang et al, ). Wet upwelling originating from the Farallon slab could hydrate the lithosphere beneath the passive continental margin (Van der Lee et al, ) and contribute to seismicity in the NMSZ (Chen et al, ; Nyamwandha et al, ) and even central Wyoming (Craig & Heyburn, ; Frohlich et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%